Lupus mastitis with predominant kappa-restricted plasma cell infiltration: report of a rare case - Mingfei Yan; Philip Bomeisl; Hannah Gilmore; Kwadwo Oduro; Aparna Harbhajanka (BMC, 2020)
Abstract Lupus mastitis (LM) is a rare complication of systemic lupus erythematosus (SLE) or discoid lupus erythematosus (DLE). The clinical presentations of LM may mimic breast malignancy, and biopsy or excision is usually performed. Histologically, LM is featured by lymphoplasmacytic inflammation involving breast ducts, lobules, blood vessels and adipose tissue. Characteristic hyaline fat necrosis can be noted in most cases. Here, we reported a case of LM in an elderly female patient who presented with bilateral breast lesions. Histologically, the breast lesions showed prominent hyaline fat necrosis and predominantly plasmacytic inflammation involving breast ducts, vessels and fat lobules. Fibrinoid necrosis of vessels was also noted. The infiltrated plasma cells were Kappa light chain-restricted, but did not show the immunophenotypes for a plasma cell neoplasm. In addition, the patient developed Kappa-restricted plasma cell myeloma 2 years later. The patient was followed up for 8 years, and her breast lesion did not show recurrence. The patient's unique clinicopathological presentations indicated a potential correlation between her LM and subsequently developed myeloma. It also indicated that the immunophenotypical characterization of infiltrated plasma cells in LM patients with predominant plasma cell infiltration may be important to rule out potential plasma cell neoplasms.